Pentagram: Komposisi Musik Hibrid dengan Konsep Modulasi Berbentuk Pentagram - Yudhistira, I Gede Raditya; Wiyati, Wahyu Sri; Sudirana, I Wayan (Journal of Music Science, Technology, and Industry, 2021)
Purpose: This article is used to introduce musical compositions that use a pentagram-shaped modulation system on top of the Circle of Fifth system which later forms the modulation of Ab-C-E-Bb-D. This Pentagram work is a work that consists of three parts with a solo performance format. Research method: Pentagram musical works refer to five initial stages, namely preparation, elaboration, synthesis, concept realization, and completion. Results and discussion: Pentagram musical works consist of three parts, with different interpretations but in one unit. The work of Pentagram is a hybrid music that mixes traditional Balinese music idioms and Western music idioms. Implication: The cultivators borrowed Balinese musical idioms such as the kendang kerumungan pattern, the Kotekan pattern, the pelog and selendro laras (scales). The cultivators also borrowed western music idioms such as Polyrhythm, Metric Modulation, and borrowed some minimalist music techniques such as Ostinato.